Emily Johansen. Beyond Safety: Risk, Cosmopolitanism, and Contemporary Neoliberal Life. Bloomsbury, 2021. - Irene Gammel; Jason Wang (Studies in 20th & 21st Century Literature, 2022)
Review of Emily Johansen. Beyond Safety: Risk, Cosmopolitanism, and Contemporary Neoliberal Life. Bloomsbury, 2021. xiii + 171 pp.
Keywords: cosmopolitanism; literature; culture; food; viral infection; climate change; individualism